Multicenter Prospective Cohort Study on Volume Management After Subarachnoid Hemorrhage: Hemodynamic Changes According to Severity of Subarachnoid Hemorrhage and Cerebral Vasospasm - Yoneda, Hiroshi; Nakamura, Takumi; Shirao, Satoshi; Tanaka, Nobuhiro; Ishihara, Hideyuki; Suehiro, Eiichi; Koizumi, Hiroyasu; Isotani, Eiji; Suzuki, Michiyasu (Stroke (1970), 2013)
BACKGROUND AND PURPOSE—Systemic circulation management has not been established for patients with poor grade aneurysmal subarachnoid hemorrhage (SAH) or delayed cerebral ischemia (DCI) after SAH. The aims of the study were to examine hemodynamic variables in these patients and to establish treatment strategies. METHODS—A multicenter prospective cohort study of hemodynamic variables from days 1 to 14 was performed using a transpulmonary thermodilution system (PiCCO Plus). Parameters were analyzed by Mann–Whitney test. Multivariate analysis was performed to identify parameters involved in onset of DCI. RESULTS—The subjects were 204 patients, including 138 with poor grade SAH (World Federation of Neurological Surgeons grades IV and V) and 52 who developed DCI. The extravascular lung water index, pulmonary vascular permeability index, and systemic vascular resistance index were significantly greater in patients with poor grade SAH compared with those with good grade SAH (World Federation of Neurological Surgeons I–III) on day 2 (P=0.049, P=0.039, and P=0.038). Cardiac index was significantly lower in patients with poor grade SAH on days 1 and 2 (P=0.027 and P=0.011). In patients with DCI, the global end-diastolic volume index was significantly lower than in those without DCI on days 3 to 5 (P=0.0053; P=0.048; and P=0.048). In multivariate analysis, median global end-diastolic volume index, cardiac index, and systemic vascular resistance index at an early stage of SAH (days 3–6) were independently related to onset of DCI (P=0.023, P=0.013, and P=0.003). CONCLUSIONS—Patients with poor grade SAH developed heart failure–like afterload mismatch at an early stage, and those with DCI had decreased global end-diastolic volume index (hypovolemia) in the early stage of SAH. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierUMIN000003794.